Double effects of the pandemic (corona) - Mitrović, Veselin (Sociološki pregled, 2020)
In this paper, we start from a clear distinction between “disaster” and “crisis”. In this regard, the basic hypotheses of this paper are that the double effects of a disaster can be understood in two ways. The first, broader view of these effects refers to crises. In the second case, the double effect can be taken literally, i.e. as a result of a direct response to a pandemic. We will analyse both cases in this text from a bioethical perspective. In this sense, the medical response to the virus can lead not only to the treatment of the consequences of the disease but also to „Enhancement of the human species“ in order to resist this or a similar virus.
Keywords: disaster; crisis; biоеthics; coronavirus; pandemic